Mental practice for treating upper extremity deficits in individuals with hemiparesis after stroke - Barclay‐Goddard, Ruth E (Cochrane Database Syst Rev, 2011)
BACKGROUND: Activity limitations of the upper extremity are a common finding for individuals living with stroke. Mental practice (MP) is a training method that uses cognitive rehearsal of activities to improve performance of those activities. OBJECTIVES: To determine if MP improves the outcome of upper extremity rehabilitation for individuals living with the effects of stroke. SEARCH METHODS: We searched the Cochrane Stroke Group Trials Register (November 2010), the Cochrane Central Register of Controlled Trials (CENTRAL) (The Cochrane Library, November 2009), PubMed (1965 to November 2009), EMBASE (1980 to November 2009), CINAHL (1982 to November 2009), PsycINFO (1872 to November 2009), Scopus (1996 to November 2009), Web of Science (1955 to November 2009), the Physiotherapy Evidence Database (PEDro), CIRRIE, REHABDATA, ongoing trials registers, and also handsearched relevant journals and searched reference lists. SELECTION CRITERIA: Randomised controlled trials involving adults with stroke who had deficits in upper extremity function. DATA COLLECTION AND ANALYSIS: Two review authors independently selected trials for inclusion. We considered the primary outcome to be the ability of the arm to be used for appropriate tasks (i.e. arm function). MAIN RESULTS: We included six studies involving 119 participants. We combined studies that evaluated MP in addition to another treatment versus the other treatment alone. Mental practice in combination with other treatment appears more effective in improving upper extremity function than the other treatment alone (Z = 3.48, P = 0.0005; standardised mean difference (SMD) 1.37; 95% confidence interval (CI) 0.60 to 2.15). We attempted subgroup analyses, based on time since stroke and dosage of MP; however, numbers in each group were small. We evaluated the quality of the evidence with the PEDro scale, ranging from 6 to 9 out of 10; we determined the GRADE score to be moderate. AUTHORS' CONCLUSIONS: There is limited evidence to suggest that MP in combination with other rehabilitation treatment appears to be beneficial in improving upper extremity function after stroke, as compared with other rehabilitation treatment without MP. Evidence regarding improvement in motor recovery and quality of movement is less clear. There is no clear pattern regarding the ideal dosage of MP required to improve outcomes. Further studies are required to evaluate the effect of MP on time post stroke, volume of MP that is required to affect the outcomes and whether improvement is maintained long‐term. Numerous large ongoing studies will soon improve the evidence base.